2013
DOI: 10.1016/j.chemosphere.2013.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity and fungal deterioration of recycled polypropylene/wood composites: Effect of wood content and coupling

Abstract: Polypropylene (PP)/wood composites were produced by homogenization in a twin-screw extruder and injection molding of tensile bars. Their mechanical properties were determined before and after exposure to biological treatment, and the effect of the treatment was assessed by various ways including visual inspection and the measurement of weight loss. The ecotoxicity of the materials was also evaluated by using the bioluminescent bacteria Vibrio fischeri. The results proved that wood facilitates biodeterioration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This was explained by the later fraction’s longer contact time in the leaching phase and by the swelling of the coatings. Sudár et al [ 61 ] used different dilutions of the eluates for ecotoxicity testing and established dose–response curves. These curves were used to calculate the eluate dilution where 50% of the effect is observed (EC 50 ).…”
Section: Ecotoxicity Testsmentioning
confidence: 99%
“…This was explained by the later fraction’s longer contact time in the leaching phase and by the swelling of the coatings. Sudár et al [ 61 ] used different dilutions of the eluates for ecotoxicity testing and established dose–response curves. These curves were used to calculate the eluate dilution where 50% of the effect is observed (EC 50 ).…”
Section: Ecotoxicity Testsmentioning
confidence: 99%
“…Higher wood contents always increase the fungal susceptibility of WPCs due to wood fiber metabolization by fungus and microorganism, 13,[21][22][23] which then lend to larger weight reductions or more colonization for composites. 24 However, the results of studies about the effects of wood particle size on fungal resistance of WPCs are divergent. Verhey and Laks 25 found that increasing wood particle size resulted in an increasing of weight losses in WPCs due to fungal decay, which probably because of a more effective encapsulation of smaller wood particles by the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting fungal and fire resistance include type of polymer, wood/polymer ratio, wood species, and other additives. Previous research has found that zinc borate (ZnB) has various functions, including serving as an antifungal agent and flame retardant, as well as being less soluble. It also has a high processing temperature and is low‐cost and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been carried out on deterioration of WPC materials by fungal decay. Sudár et al studied the effects of wood content on fungal deterioration of recycled polypropylene/wood composites against a mixture of soft‐rot and stain fungi. The results suggested that wood facilitated fungal colonization, causing slight weight loss of <3%, but it was not correlated with substantial deterioration in material properties.…”
Section: Introductionmentioning
confidence: 99%